A new modified speculum guided single nostril technique for endoscopic transnasal transsphenoidal surgery: an analysis of nasal complications. (December 2013) - Waran, Vicknes; Tang, Ing Ping; Karuppiah, Ravindran; Abd Kadir, Khairul Azmi; Chandran, Hari; Muthusamy, Kalai Arasu; Prepageran, Narayanan
Abstract The endoscopic transnasal, transsphenoidal surgical technique for pituitary tumour excision has generally been regarded as a less invasive technique, ranging from single nostril to dual nostril techniques. We propose a single nostril technique using a modified nasal speculum as a preferred technique. We initially reviewed 25 patients who underwent pituitary tumour excision, via endoscopic transnasal transsphenoidal surgery, using this new modified speculum-guided single nostril technique. The results show shorter operation time with reduced intra- and post-operative nasal soft tissue injuries and complications.